Race Talk Moves for Racial Literacy in the Elementary Classroom. (December 2022) - Daly, Annie
The study examines how a white elementary educator used discursive practices I refer to as "race talk moves" to support students' racial literacy during whole-class read-alouds. This case study found that the teacher used four moves that have been previously documented in literature discussions: listening, participating, synthesizing, and challenging. Significantly, however, the teacher drew upon these moves in ways that were responsive to students' racialized identities and emergent understandings of race. Moreover, the analysis identified a new, fifth move, what I call "anchoring, " that supported students in moving from surface-level conceptions of race to a deeper understanding of systemic racism. By actively responding to and deepening students' racial literacy contributions, anchoring moves illuminate how teachers and students can co-construct critical race knowledge. This study diverges from previous research on the drawbacks of white teachers talking about race to demonstrate the moves teachers can make to support students' racial literacy development.